2010
DOI: 10.2527/jas.2010-3250
|View full text |Cite
|
Sign up to set email alerts
|

Unwanted horses: The role of nonprofit equine rescue and sanctuary organizations1

Abstract: Closure of US equine slaughter facilities in 2007 along with the concomitant economic recession have contributed to a sharp increase in the number of unwanted horses throughout the United States, with estimates totaling 100,000 horses per year. The objective of the study was to obtain comprehensive data regarding nonprofit organizations caring for unwanted horses, along with the characteristics and outcome of horses relinquished to these organizations. Nonprofit organizations that accept relinquished equines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 2 publications
0
27
1
Order By: Relevance
“…There was a study conducted that evaluated the effects of the financial crisis as part of the reason for the sharp increase in the number of unwanted horses in the United States (Holcomb, Stull, & Kass, 2010). However, owners who selected finances or moving as reasons for relinquishing their dogs were as likely to have another dog remaining in their household as those who did not select those reasons for relinquishment.…”
Section: Discussionmentioning
confidence: 99%
“…There was a study conducted that evaluated the effects of the financial crisis as part of the reason for the sharp increase in the number of unwanted horses in the United States (Holcomb, Stull, & Kass, 2010). However, owners who selected finances or moving as reasons for relinquishing their dogs were as likely to have another dog remaining in their household as those who did not select those reasons for relinquishment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the records, 70% were western type horses, 11% were English or Thoroughbred type horses, 3.6% were draft type horses, and the rest included other breeds or types of horses or mules [109,110]. In a separate study of non-profit organizations (not necessarily breed-specific) that accepted relinquished horses, respondents reported that relinquished horses consisted of mostly light horse breeds (79.3%), with Thoroughbreds (21.6%) and Quarter Horses (18.9%) as the most represented breeds [111]. Taken together, these studies suggest that Thoroughbreds may not be the most prevalent breed present in processing plants or non-profit organizations; however, the public expects the industry to retain the responsibility to ensure humane living circumstances once a horse's racing and breeding careers are over.…”
Section: Aftercarementioning
confidence: 99%
“…Financial hardship, physical inability or lack of time to care for the horses by owners were the most common reasons for relinquishment, followed by seizure through law enforcement agencies for alleged neglect or abuse. The overall distribution of unwanted equids was comparable with the general US population [12]. …”
Section: Introductionmentioning
confidence: 99%